Effect of Durian Peel and Young Coconut Shell Composition on the Quality of Biomass Briquettes as Alternative Fuel - Marwanto, Andriana; Adeko, Riang; Mualim, Mualim; Ganefati, Sri Puji; Hidayat, Habibi (Universitas Muhammadiyah Prof. Dr. Hamka, 2026)
Background: The use of fossil fuels can cause various impacts that lead to health problems. Therefore, an alternative energy source is needed to reduce environmental impact. One form of biomass energy is briquette production. Briquette materials can be obtained from industrial waste, namely durian peels and young coconut shells. Methods: This study employed a laboratory-scale experimental design to evaluate the effect of material composition on briquette quality parameters. Results: The results showed that variations in the composition of durian peel and young coconut shells produced different briquette qualities for each parameter, with a 2:1 mixture providing the most optimal quality with low moisture content (3.91%), low ash content (6.52%), high fixed carbon (85.04%), controlled volatile matter (4.53%), and high calorific value (6096 cal/g). The ANOVA test showed p-values < 0.05 for all quality parameters, indicating that variations in material composition significantly affect the quality of the briquettes produced. Conclusions: This research indicates that the quality of briquettes made from a mixture of durian peel and young coconut shells is influenced by composition, with a 2:1 ratio producing the best quality based on parameters such as moisture content, ash content, bound carbon, volatile matter, and calorific value. Further research is recommended using a wider range of ratios and additional testing, such as durability and combustion emissions, to strengthen the assessment of briquette quality.